Comparison of social representations of NEETs in active young French adults and NEETs themselves. Issue 3 (4th May 2021) - Dumouilla, Auguste; Botella, Marion; Gillet, Maxime; Joncheray, Hélène; Guegan, Jérôme; Robieux, Léonore; Bordes, Pascal; Collard, Luc; Hodzic, Sabina; Sovet, Laurent; Lubart, Todd; Zenasni, Franck
ABSTRACT: Although diverse European policy initiatives have been developed to integrate young NEETs – "Not in Employment, Education or Training", it is particularly relevant to question how NEETs are perceived by their counterparts who are actively engaged in society. For this reason, we aimed to examine the Social Representations (SRs) of NEETs in France, using the classic free evocation technique. French NEETs ( n = 71) and matched controls ( n = 66; people employed, in education or in training) were interviewed. Results showed the scope of SRs for the semantic field of the term NEET and its associated terms. The need to develop effective communication to talk about work, education, and training with NEETs and implications for career counselling are discussed.